The Roles of Sclerostin in Immune System and the Applications of Aptamers in Immune-Related Research - Sun, Meiheng; Chen, Zihao; Wu, Xiaoqiu; Yu, Yuanyuan; Wang, Luyao; Lu, Aiping; Zhang, Ge; Li, Fangfei (Frontiers in Immunology, 2021)
Wnt signaling is one of the fundamental pathways that plays a major role in a large body of biological systems. In addition to the well-known influence of Wnt signaling on bone formation, its essential role in the immune system also attracted increasing appreciation. Sclerostin, a confirmed Wnt antagonist, is also proven to modulate the development and differentiation of normal immune cells, particularly B cells. Aptamers, single-stranded (ss) oligonucleotides, are capable of specifically binding to a variety of target molecules by virtue of unique three-dimensional structure. With in-depth study of those functional nucleic acids, they have been gradually applied to diagnostic and therapeutic area in massive immune diseases due to their various advantages over antibodies. In this review, we focus on elaborating several parts including the roles of Wnt signaling and Wnt antagonist sclerostin in the immune system. For the sake of understanding, current examples of aptamers applications for the immune diseases are also provided. At the end of this review, we propose our ideas towards the future research directions.